2020
DOI: 10.1021/acssuschemeng.0c06316
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Extraction by Manothermosonication: Recapturing the Value of Pomegranate Peels and Nanocomplexation of Extracts with Pea Protein

Abstract: Manothermosonication (MTS) is a treatment that combines ultrasonication with mild temperature and pressure. MTS extraction was evaluated for recapturing bioactive compounds of pomegranate peel waste. The influence of extraction time (0.5−3 min), temperature (25−50 °C), and pressure (100−500 kPa) on the yield of total phenolic content (TPC) and antioxidant activity (AOA) was assessed. Pea protein isolates (PPIs) and PPI-modified starch (PPI-S) were used to form nanocomplexes with the phenolic extract (PE). Lyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For the extracts obtained using seven different solvents, TPC was determined spectrophotometrically by the Folin-Ciocalteu method [29,30]. First, 100 μL of the extract was diluted 10 times and 2.5 mL of Folin solution (0.2 N) were mixed and left for 3 minutes.…”
Section: Determination Of Tpc By Folin-ciocalteu Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the extracts obtained using seven different solvents, TPC was determined spectrophotometrically by the Folin-Ciocalteu method [29,30]. First, 100 μL of the extract was diluted 10 times and 2.5 mL of Folin solution (0.2 N) were mixed and left for 3 minutes.…”
Section: Determination Of Tpc By Folin-ciocalteu Methodsmentioning
confidence: 99%
“…For example, Satpati et al investigated the inhibition efficiency of the synthesized vanillin-based Schiff base for mild steel in 1 M HCl. They reported that it was adsorbed on the metal surface by chemical adsorption via the vanillin moiety and the imine group [28][29][30]. Currently, there is no generally accepted method for the recovery of all or a particular group of phenolic compounds in the five main groups called phenolic acids, flavonoids, tannins, phenolic ligands, and stilbene derivatives due to the complex structure of plants.…”
Section: Extraction Of Walnut Shellsmentioning
confidence: 99%
“…The Folin-Ciocalteu colorimetric method was used to determine the total phenolic content (TPC), as described by Güzel et al (2020) with minor modifications. Extraction of bioactive compounds was performed using a 1:10 (w/v) solid solvent ratio, 37 kHz frequency, and 100% amplitude in an ultrasonic bath (Sonorex DigiPlus DL 255 H) for 20 min.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…The pomegranate fruit mainly consisted of seeds, pulp, and skins, among which the skins accounted to 40–50% of the total fruit . Factory work would generate huge amounts of industrial pomegranate skins (PS; skins, 78% and seeds, 22%), which could exert much pressure to the environment since the industrial wastes were much tricky to dispose and contained many antioxidants, resulting in oxygen depletion and environmental pollution. In fact, the PS contained the rich compound polyphenols so that the PS could be a cheap and convenient source of polyphenols, thus addressing the environmental concerns. , Polyphenols, the secondary metabolite in plants, were prevalently recognized antioxidants and were widely used in anti-inflammation, chronic diseases, oral health, anti-cancer, and so on. Although nowadays, some polyphenols could be synthesized chemically, and the acceptability was challenged due to consumer concerns about safety. , Therefore, including cosmetics, pharmaceutical, and the food industry, huge markets of natural polyphenols existed to provide confidence for natural polyphenol extraction, which could be the potential method for PS valorization for considerable health, environmental, and profit benefits. , …”
Section: Introductionmentioning
confidence: 99%